Polluting our prisons? An examination of Oklahoma prison locations and toxic releases, 2011–2017. (October 2020) - Leon-Corwin, Maggie; McElroy, Jericho R; Estes, Michelle L; Lewis, Jon; Long, Michael A
Recent research has highlighted numerous environmental concerns with US prisons, including that prisons are often located on undesirable land that is in close proximity to environmental hazards. We utilize an environmental justice and green criminology perspective to test this in Oklahoma using data on prison sites and toxic releases provided by the US Environmental Protection Agency for a period of seven years (2011–2017). We focus on Oklahoma because it recently became the state with the highest overall incarceration rate and has a history of elevated levels of pollution. Our results find that prison zip codes have greater TRI emissions compared to non-prison zip codes. We conclude with a discussion of the implications of the study and directions for future research.